Enhanced catalytic activity of polyethylenedioxythiophene towards tri-iodide reduction in DSSCs via 1-dimensional alignment using hollow carbon nanofibers - Anothumakkool, Bihag; Game, Onkar S.; Bhange, Siddheshwar N.; Kumari, Tanya; Ogale, Satishchandra B.; Kurungot, Sreekumar (Nanoscale, 2014)
Here, we report a highly conducting 1-dimensionally (1-D) aligned polyethylenedioxythiophene (PEDOT) along the inner and outer surfaces of a hollow carbon nanofiber (CNF) and its application as a counter electrode in a dye sensitized solar cell (DSSC). The hybrid material (CP-25) displays a conversion efficiency of 7.16% compared to 7.30% for the standard Pt counter electrode, 4.48% for bulk PEDOT and 5.56% for CNF. The enhanced conversion efficiency of CP-25 is attributed to the accomplishment of high conductivity and surface area of PEDOT through the 1-D alignment compared to its bulk counterpart. Reduced charge transfer resistance and high conductivity of CP-25 could be proven by cyclic voltammetry, impedance analysis and Tafel experiments. Further, through a long-term stability test involving efficiency profiling for 20 days, it is observed that CP-25 possesses excellent durability compared to the bulk PEDOT.

ZnO(N)-Spiro-MeOTAD hybrid photodiode: an efficient self-powered fast-response UV (visible) photosensor - Game, Onkar; Singh, Upendra; Kumari, Tanya; Banpurkar, Arun; Ogale, Satishchandra (Nanoscale, 2014)
Organic-inorganic hybrid photo-detectors with a self-sufficient mode of operation represent a research area of great current interest. In most efficient photodetectors and optoelectronic devices compound semiconductors containing toxic elements such as Cd, As, Te, S, Se etc. are used and these are also expensive. Hence there is also a rapidly growing interest in replacing these with environmentally friendly and earth-abundant materials. Herein, we report a facile solution-processed fabrication of a self-powered organic-inorganic hybrid photodetector using n-type oriented ZnO nanorods and p-type Spiro-MeOTAD semiconductor. ZnO is eco-friendly and earth-abundant, and Spiro-MeOTAD is nonhazardous. We show that the latter has far less toxicity than the toxic elements stated above. This visible blind UV photodetector shows high sensitivity (10(2)) and a UV/visible rejection ratio of 300. It also exhibits fast response times of tau(rise) similar to 200 mu s and tau(fall) similar to 950 mu s. Importantly, with a small modification of nitrogen incorporation in ZnO one can also realize a highly-sensitive self-powered visible light photodetector with at least 1000% (or higher) improvements in quality factors (photocurrent/sensitivity/response time) as compared to previously reported organic-inorganic hybrid photo-detectors based on metal-chalcogenides (CdS-PANI or CuInSe2-P3HT). Interestingly, the broadband sensitivity of such N:ZnO-Spiro-MeOTAD photodiode enables sensing of low intensity (similar to 28 mu W cm(-2)) ambient white light with a high photocurrent density of 120 nA cm(-2) making it an efficient ambient white light detector.

Significance of secondary forces toward improving the charge carrier mobility of Isoindigo based conjugated small molecules - Dharmapurikar, Satej S.; Kashmir, Arulraj Arul; Kumari, Tanya; Kalalawe, Virbhadra; Kanetkar, Maruti; Chini, Mrinmoy Kumar (Chemical Physics Letters, 2021)
The charge carrier mobility of conjugated small molecules (CSMs) depends on the intermolecular interactions and morphology. Herein, we report the synthesis of CSMs having different side chains. Hydrogen bonding, lipophilic imbalance and van der Waals interactions are imparted through the asymmetric substitution of Isoindigo. The secondary forces impact thin film morphology, and charge carrier mobility. The CSMs having van der Waals interaction further shows higher charge carrier mobility as a function of improved morphology, and increased temperature. The highest mobility of 0.15 cm2/Vs has been achieved for CSMs with van der Waals interaction.
Keywords: Conjugated small molecules; Isoindigo; mobility; OFET; Secondary force